Understanding brain aging and dementia : a life course approach - Whalley, Lawrence J. (Columbia University Press, 2015)
The life course method compares an individual's long-life and late-life behaviors to gauge one's mental decay. Arguing the life course approach is the best and simplest model for tracking mental development, Lawrence J. Whalley unlocks the mysteries of brain functionality, illuminating the processes that affect the brain during aging, the causes behind these changes, and effective coping strategies. Whalley identifies the genetic factors that determine the pace of aging and the behaviors, starting in childhood, that influence how we age. Through vignettes, charts, and tables, he composes an ac.